Prinsip-prinsip Islam Tentang Demokrasi : Studi Pemikiran Nurcholish Madjid Tahun 1970-2005 - Akmal Hawi (Medina-te : Jurnal Studi Islam, 2019)
This article is a summary of research results written using descriptive and holistic methods. By reviewing primary and secondary sources to obtain accurate and clear data that contains: Islamic principles of democracy in the struggle of Nurcholish Madjid, Islamic Principles about Democracy in Learning Applying Islamic Principles about democracy in Indonesia. Democracy requires real effort from every citizen and its supporting devices, namely a conducive culture as a manifestation of a society's thinking and design to create democracy as a view of life in the country both by the people and the government. The regularity of the background, the importance of this article is discussed. This article will discuss more about discussing Nurcholish Madjid about Islam and democracy.